The evaluation of spatial variation of water quality in Sungai Setiu Basin, Terengganu - Izyan Munirah M. Zaideen,; Suhaimi Suratman,; Norhayati Mohd Tahir, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study investigates the spatial variation of water quality parameters in Sungai Setiu Basin at ten different locations from March 2010 to February 2011. The water quality was assessed using the Water Quality Index by Malaysian Department of Environment (DOE-WQI) and classified according to the Malaysia Interim National Water Quality Standard (INWQS). Six water quality parameters embedded in the DOE-WQI were dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, ammoniacal nitrogen (AN) and total suspended solid (TSS). In addition, this study also examined the changes in water quality over the past 10 years by comparing the present water quality to the previous works. The overall mean WQI value obtained was 84.0 which indicate that the Sungai Setiu basin is in clean condition and all measured water quality parameters gave value within the permissible limits of the INWQS classification except for pH which fall in Class III. It can be concluded that water quality in Sungai Setiu does not varies greatly over a decade. Hence continuous monitoring is needed to improve the water quality and minimize water pollution.